Arnold-Chiari Malformation Type II and CYP1B1 Congenital Glaucoma: A Possible Association - Shaikha Aldossari; Amani Al Bakri; Yumna Kamal (Case Reports in Ophthalmological Medicine)
Background. We describe a case of an infant with Arnold-Chiari Malformation Type II (ACM-II) who was born with lumbosacral myelomeningocele, hydrocephalus, and primary congenital glaucoma (PCG) together with dysmorphic features (scaphocephaly, frontal bossing, hypotelorism, entropion, and flat nasal bridge), which according to our knowledge, is a combination that has yet to be described in literature. Primary diagnosis. A 2-year-old female who is known to have ACM-II was referred due to abnormal eye examination done in a peripheral hospital that suggested infantile glaucoma in both eyes. Findings. During her last physical exam (postop), she was vitally stable, conscious with good feeding. Ophthalmic assessment revealed buphthalmia, superior paracentral scar, deep anterior chambers (AC), and round pupils with positive red reflex, clear lens, and an IOP of 16, 14 mm Hg, respectively. Neurological exam showed paraparesis and moving upper extremities and has axial hypotonia. Genetic testing showed CYP1B1 gene mutation. Conclusion. The aim of reporting this case is to share the findings in this infant as it may be a new association. The main learning message here is that ACM-II patients may present with certain ocular symptoms, including glaucoma-related ones that may mimic neurological disorders. This report brings information that could alert general practitioners, neurologists, and neurosurgeons. A deeper understanding of this rare disorder may aid the diagnosis of cases with similar characteristic physical findings by referring them to an ophthalmology clinic for further evaluation. Case presentation. A 2-year-old female who is known to have Arnold Chiari Malformation Type II (ACM- II) was referred due to abnormal eye examination done in a peripheral hospital that suggested infantile glaucoma in both eyes. MRI at 3 months of age showed lumbosacral myelomeningocele and hydrocephalus. Genetic testing confirmed a CYP1B1 mutation. These combinations of symptoms were never described in the literature before.